Simultaneous Bilateral Neck of Femur Fracture in a Young Adult with Underlying Metabolic Disturbances - Eslam Alkaramani (14570439) (2020)
Introduction. Simultaneous bilateral fractures of the femoral neck are considered very rare injuries. Few cases were reported in the literature. Most cases were reported in elderly patients with underlying bone pathology. Case Report. We report a case of a 31-year-old male patient who presented to the emergency department with bilateral hip pain and inability to bear weight after a sudden loss of consciousness and fall while running on a treadmill. The patient had a recent history of anabolic steroids, growth hormone, and other supplements used for bodybuilding. Radiological studies confirmed bilateral neck of femur fracture. Laboratory investigations revealed pan-pituitary axis insufficiency and mild vitamin D deficiency, and his EEG suggested a seizure attack. The patient was treated with three 6.5 mm cannulated cancellous screws on one side and a sliding hip screw on the other side and was followed with strict physical therapy and rehabilitation plan. 6 months from the injury, a radiographic bilateral union achieved with the patient back to his normal daily activity and noncontact sports. Conclusion. We report this rare case of bilateral neck of femur fracture in a young adult after a generalized seizure attack with underlying metabolic disturbances. Ruling out other biological underlying etiologies, early diagnosis and early fracture anatomic reduction and fixation are crucial to decrease potential complications such as avascular necrosis and fracture nonunion.  Other information  Published in: Case Reports in Orthopedics License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1155/2020/8972542